Pengembangan Kawasan Wisata Berkelanjutan - Desvirah Gita Arista; Slamet Trisutomo; Baharuddin Koddeng (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
The tourism sector is one of the leading sectors in the national economy that always needs to be developed. Makassar City has many tourism potentials that can be developed, one of which is the tourism potential found in the Balang Beru River. Balang Beru River is a river that originated from the Jeneberang River and empties into Losari Beach. The river passes through the Somba Opu area as a cultural area and Lake Tanjung Bunga as an integrated sports and tourism area. This study aims to identify the characteristics of tourist area and develop the concept of sustainable tourism development in the Balang Beru River. The analytical method used in this research is descriptive qualitative, comparative, and spatial analysis through photo mapping. The results of this study indicate that the characteristics of tourism in the form of attractions, accessibility, and facilities. Location attractions are divided into two namely, on land and on water. In addition, this location can be accessed by several roads making it easier for visitors or tourists to get to their destination. Meanwhile, the facilities available in the form of lodging, restaurants or restaurants, tourist information offices, gift shops, and so on. The direction of the concept of sustainable tourism development, among others, the utilization of the potential contained on the banks of the river to support tourism activities, procurement of supporting facilities and infrastructure, zoning distribution of tourism namely the zone of water sports tourism, water recreation tourism and cultural tourism.